The Effect of Annealing on the Microstructure and Properties of Ultralow-Temperature Rolled Mg–2Y–0.6Nd–0.6Zr Alloy - Hongmin Yu; Wei Li; Yun Tan; Yuanbiao Tan (Metals, 2021)
Mg–2Y–0.6Nd–0.6Zr alloy was first deformed by equal channel angular pressing (ECAP), then rolled and deformed under ultralow temperature conditions (liquid nitrogen immersion), and finally annealed. Optical microscopy (OM), electron backscatter diffraction technology (EBSD), and transmission electron microscopy (TEM) were used to analyze the evolution of the multiscale microstructure and changes in the mechanical properties of the alloy under ultralow temperatures and various annealing conditions. The results showed that the alloy treated with ECAP obtained fine grains, and a large number of fine twins were formed during the ultralow-temperature rolling process, which promoted the improvement of its hardness and strength and provided numerous preferential nucleation sites. The annealing made it easier to induce recrystallization and improve the recrystallization nucleation rate. The twin boundary produced by the alloy after ultralow-temperature rolling and the uniform fine grains formed by annealing resulted in excellent strength and plasticity of the alloy. The twins formed after rolling under ultralow temperatures were mainly {<semantics>10<mover>1-</mover>2</semantics>} <<semantics><mover>1-</mover>011</semantics>> tensile twins. The alloy had comprehensive mechanical properties with a tensile strength of 186.15 MPa and an elongation of 29% after annealing at 350 °C for 10 min.